LANGUAGE KINSHIP BETWEEN MANDARIN, HOKKIEN CHINESE AND JAPANESE (LEXICOSTATISTICS REVIEW) - Abdul Gapur; Dina Shabrina Putri Siregar; Mhd Pujiono (Aksara, 2018)
Mandarin and Hokkien Chinese are well known having a tight kinship in a language family. Beside, Japanese also has historical relation with China in the eld of language and cultural development. Japanese uses Chinese characters named kanji with certain phonemic vocabulary adjustment, which is adapted into Japanese. This phonemic adjustment of kanji is called Kango. This research discusses about the kinship of Mandarin, Hokkien Chinese in Indonesia and Japanese Kango with lexicostatistics review. The method used is quantitative with lexicostatistics technique. Quantitative method nds similar percentage of 100-200 Swadesh vocabularies. Quantitative method with lexicostatistics results in a tree diagram of the language genetics. From the lexicostatistics calculation to the lexicon level, it is found that Mandarin Chinese (MC) and Japanese Kango (JK) are two different languages, because they are in a language group (stock) (29%); (2) JK and Indonesian Hokkien Chinese (IHC) are also two different languages, because they are in a language group (stock) (24%); and (3) MC and IHC belong to the same language family (42%).